Biobutanol Production from Microalgae Nannochloropsis sp. Biomasses by Clostridium acetobutylicum Fermentation - Onie Kristiawan; Usman Sumo Friend Tambunan (Testing Center for Oil and Gas LEMIGAS, 2020)
Biobutanol is an example of alternative energy sources to replace liquid fuel with the carbon-neutral characteristic. It has more benefits to the environment compared to the fossil fuel. Biobutanol is synthesized through fermentation of microalgae cells wall or other organism parts as the carbon sources. The aim of this study is to determine the ability of Clostridium acetobutylicum bacteria in the fermentation of Nannochloropsis sp. to produce biobutanol. Fermentation of Nannochloropsis sp. for biobutanol production was used as an initial treatment before lipid extraction. Fermentation was performed with C. acetobutylicum bacteria for 96 hours. The result showed that C. acetobutylicum was able to produce 2.61% v/v butanol. Thisprocess used Nannochloropsis sp. microalgae hydrolysates and biomass of viscozyme hydrolysis yield. The process of hydrolysis with cellulose and viscozyme can produce simple sugars, with the highest obtained yield of 1738.38 ppm from hydrolysis using viscozyme.